A Network Perspective on Individual-Level Ambidexterity in Organizations - Rogan, Michelle; Mors, Marie Louise (Organization Science, 2014)
Addressing the call for a deeper understanding of ambidexterity at the individual level, we propose that managers’ networks are an important yet understudied factor in the ability to balance the trade-off between exploring for new business and exploiting existing business. Analyses of 1,449 ties in the internal and external networks of 79 senior managers in a management consulting firm revealed significant differences in the density, contact heterogeneity, and informality of ties in the networks of senior managers who engaged in both exploration and exploitation compared with managers that predominately explored or exploited. The findings suggest that managers’ networks are important levers for their ability to behave ambidextrously and offer insights into the microfoundations of organizational ambidexterity.